Intraoperative near‐infrared fluorescence imaging of parathyroid adenomas with use of low‐dose methylene blue. Issue 6 (4th October 2013) - van der Vorst, Joost R.; Schaafsma, Boudewijn E.; Verbeek, Floris P. R.; Swijnenburg, Rutger‐Jan; Tummers, Quirijn R.J.G.; Hutteman, Merlijn; Hamming, Jaap F.; Kievit, Job; Frangioni, John V.; van de Velde, Cornelis J.H.; Vahrmeijer, Alexander L.
Abstract Background Intraoperative identification of parathyroid adenomas can be challenging. We hypothesized that low‐doses methylene blue (MB) and near‐infrared fluorescence (NIRF) imaging could be used to identify parathyroid adenomas intraoperatively. Methods MB was injected intravenously after exploration at a dose of 0.5 mg/kg into 12 patients who underwent parathyroid surgery. NIRF imaging was performed using the Mini‐FLARE imaging system. Results In 10 of 12 patients, histology confirmed a parathyroid adenoma. In 9 of these patients, NIRF could clearly identify the parathyroid adenoma during surgery. Seven of these 9 patients had a positive preoperative 99mTc‐sestamibi single photon emission CT (SPECT) scan. Importantly, in 2 patients, parathyroid adenomas could be identified only using NIRF. Conclusion This is the first study to show that low‐dose MB can be used as NIRF tracer for identification of parathyroid adenomas, and suggests a correlation with preoperative 99mTc‐sestamibi SPECT scanning. © 2013 Wiley Periodicals, Inc. Head Neck 36: 853–858, 2014